Determination of reference values of some serum biochemical parameters of healthy Donkeys in Iraq - AL-Salmany, Alaa K. M. (The Iraqi Journal of Veterinary Medicine, 2017)
This study is conducted to establish the profile of some serum biochemicals which included creatinine, urea, glucose, total protein and albumin concentrations in 104 clinically normal donkeys (65 males and 39 females) aged 2-4 years. Animals were classified on the basis of age and sex, in Baghdad city/ Iraq. The Results showed that the, mean values ± standard error (SE) of serum creatinine and urea concentrations were as follows: Creatinine 65.55±2.01 µmol/L and urea 6.79±0.20 mmol/L, while serum concentrations of glucose, total protein and albumin were 54.7±3.09 g/dl, 123±14.3 and 3.4±0.08 mmol/L, respectively. Creatinine values showed a significant difference between 4 years and more than 4 years old subgroups. However, there were no differences in serum urea concentration between male and female and compared with biochemical ranges obtaining for another donkey breeds. This suggested that most biochemical values determined in this study serve as reference ranges for Iraqi donkey and could be used in health control and diagnosis of diseases. In conclusion a significant increase in serum creatinine was recorded at age 4 and more than 4 years as compares with serum urea and no differences in serum glucose, total protein and albumin.